Avaliação clínica dos efeitos da terapia fotodinâmica antimicrobiana no tratamento não-cirurgico da periodontite crônica - Feldman, Bianca Calil (2009)
Photodynamic therapy (PDT) basically involves a triad of light, a photosensitizer and oxygen. When combined they can produce cytotoxic agents that can cause cell death, which may represent a promising alternative for the reduction of certain periodontal pathogens, and therefore the treatment of periodontitis. The aim of this study was to evaluate the clinical effect of adjunctive PDT in the nonsurgical treatment of chronic periodontitis. A randomized-controlled trial, 15 patients with chronic periodontitis were included, and exhibited at least five periodontal pockets and clinical attachment level ≥ 5 mm. All patients received non-surgical periodontal treatment. Using a split-mouth design, test side were additionally treated with a PDT (methylene blue 0,01% + Diode Laser 660 nm). Probing pockets depth (PB), Clinical attachment levels (CAL) and Blending on probing (BOP) were assessed at baseline, 30, 60 and 90 days after therapy. The statistical results showed that all clinical parameters were significantly reduced in test and control sides after therapy. However, the intergroup difference was not significant for PBS and CAL. BOP was statistical difference intergroups in the 60 days later (p =0,048). The additional application of a PDT to nonsurgical periodontal treatment was not effective. There were no extra reductions in PBS, CAL and BOP.